Knowledge, attitude and practice of pharmacovigilance among community pharmacists in Delhi, India - Sah, Ravinder K.; Chandane, Rakhamaji D.; ., Krishna; Manocha, Sachin; Kapur, Ajita (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Lack of knowledge of Pharmacovigilance (PhV) and Adverse Drug Reactions (ADRs) reporting culture among the prescribers have been identified as major factors for under reporting of ADRs. In an attempt to increase the reporting many countries have allowed pharmacists to report ADRs. This study was planned to assess the knowledge, attitude and practices of PhV among community pharmacist in Delhi, India. Methods: Cross sectional, questionnaire based study was conducted to evaluate the knowledge, attitude and practice of PhV among 200 community pharmacists of Delhi (west Delhi) India. Results: Majority (74%) of the respondents felt that ADR reporting is necessary but only 9% were aware of existing PhV Program of India. Only 5% of pharmacists knew about elements of PhV. Forty percent (40%) of pharmacists did not know where to report ADRs and 26% felt that there is no need to report ADRs. Significant number (77%) of pharmacists felt that ADRs reporting will damage their image. 96% never try to find ADRs and in case if they get ADRs from patients, majority (95%) of them never report to anybody. Almost all (96%) of respondents cited busy schedule as the main reason for non-reporting and 86% said that it will be very convenient if ADRs are collected by someone from them. Conclusions: Community pharmacists had positive attitude towards ADRs reporting but their knowledge and practice regarding PhV need to be improved. There is a need of regular training to increase their role in PhV.